An investigation into printing pressure of 3D printed continuous carbon fiber reinforced composites. (November 2022) - Zhang, Zhongsen; Long, Yu; Yang, Zhe; Fu, Kunkun; Li, Yan
Graphical abstract: Abstract: 3D printing of continuous carbon fiber reinforced polymer (CCFRP) composites is an innovative manufacturing technology of composites. This research developed a novel 3D-printed extruder to fabricate CCFRP composites using an in-situ impregnation technique. The printed CCFRP composites present relatively low void content and competitive mechanical properties due to the well impregnation of carbon fibers. The printing pressure during the 3D printing was analyzed with an in-situ traction force monitor system. The effect of printing pressure on mechanical properties and void distribution of 3D-printed CCFRP composites was then investigated by adjusting the layer thickness. It demonstrates that a thinner printing layer can generate a larger ironing force, minimizing the void formation, thus improving the mechanical properties and surface quality of final parts. However, the large traction force would reduce the dimension accuracy. A trade-off between dimension accuracy and mechanical properties should be made when optimizing the processing parameters of 3D printing.